Referentiality and Irony in El crimen de Alberto Lobo, by Gonzalo Chacón Trejos - Camacho Guzmán, Gustavo (2017)
This article analyzes two particular aspects of the novel El crimen de Alberto Lobo, by Gonzalo Chacón Trejos. Deeming it historical, the study deals with the link between the construction of the fictional universe and the conditions of factual reality; and secondly, it examines the ironic and satirical discourse present in the novel. It alludes to the political events which occurred in Costa Rica between 1914 and 1919; that is, when Alfredo González Flores was elected president, and then overthrown in a coup by Federico Tinoco Granados, and the subsequent fall of the dictatorship.